(untitled) (International Journal of Nursing Education, 2020)
Background: Self-efficacy is defined as an individual’s belief to act. Neonatal resuscitation is a treatmentof a newborn infant that requires team collaboration and movement precision. The leadership, stafforganization and meaningful recognition are required to have good teamwork. It could increase the successrate of neonatal resuscitation. This research aims to determine the correlations among leadership, staff andmeaningful recognition to self-efficacy among nurses in the neonatal resuscitation management.Method: This quantitative study method applied a cross-sectional approach. The participants were selectedusing a random sampling technique. The respondents were 75 nurses that met the inclusion criteria. The datawas collected by a questionnaire for the nurses in the NICU room and the hospital’s perinatology. The datawas analyzed by the Pearson product-moment correlation.Results: The findings showed correlations among leadership, staff organization and meaningful recognitionof the self-efficacy among the nurses in promoting neonatal resuscitation. The leadership obtains a p score= 0.000 (<0.05). Staff organization obtains a p score = 0.000 (<0.05). Meaningful recognition obtains a pscore = 0.000 (<0.05).Conclusion: Thus, self-efficacy could be improved by involving the roles of the hospital’s managementwithin the work-environment setting. It includes leadership, staff and meaningful recognition